Formulation and Evaluation of Pulsatile Drug Delivery System of Atenolol (Journal of Basic and Applied Research in Biomedicine, 2022)
The objective of the present study was formulation and evaluation of pulsatile release tablets of Atenolol. A tablet system consisting of cores which was coated with layers of swelling and rupturable coatings. Cores containing Atenolol as model drug were prepared by direct compression with appropriate ratios of lactose and microcrystalline cellulose and then coated sequentially with different ratios of an inner swelling layer containing HPMC and an outer rupturable layer of Ethyl Cellulose. The effect of level of swelling layer and rupturable coating was investigated. The different formulation press coated by using different weight ratios of Hydroxy Propyl Methyl Cellulose (HPMC) / Ethyl Cellulose (EC) / both HPMC and EC. The optimum result was achieved in formulation containing HPMC: EC weight ratios. The F3 batch achieved a highest burst release after the lag time which is applicable pulsatile drug delivery system of Atenolol.